New Result on the Critical Exponent for Solution of an Ordinary Fractional Differential Problem - Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Cui, Y. (2017)
© 2017 Xinguang Zhang et al. We give some background of fractional Cauchy problems and correct an existing result of Cauchy problem for the fractional differential inequality, and we also give an example to illustrate our statement.